THE INFLUENCE OF RESONANT LEADERSHIP AND ORGANIZATIONAL CLIMATE ON LECTURER PERFORMANCE IN ASAHAN DISTRICT - Fajar Rezeki Ananda Lubis (Journal of Information Systems Management and Digital Business, 2024)
The role of leaders in running an organization is enormous. This is because leaders influence the decision-making in each program. Suppose there are decision-making errors, which will have fatal consequences for the company's progress. Thus, this study aims to investigate how the organizational atmosphere and resonant leadership affect the performance of academics at the Asahan Regency. This study used quantitative methodologies for data collection, and SmartPLS 3.0 software was used for SEM-Partial Least Square (PLS) data analysis procedures. Two hundred thirty permanent lecturers at the Asahan Regency served as the research sample. The research results show that resonant leadership and organizational climate significantly influence the performance of lecturers in Asahan Regency. So, it is concluded that to increase human resources, resonant leadership, and an organizational environment are needed in higher education institutions in Asahan Regency.   Keyword : Resonant Leadership, Organizational Climate, Lecturer Performance